2013
DOI: 10.1080/17470919.2013.810171
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of conceptual–emotional integration and its role in major depressive disorder

Abstract: The importance of differentiating between social concepts when appraising actions (e.g., understanding behavior as critical vs. fault-finding) and its contribution to vulnerability to major depressive disorder (MDD) is unknown. We predicted poor integration of differentiated conceptual knowledge when people with MDD appraise their social actions, contributing to their tendency to grossly overgeneralize self-blame (e.g., “I am unlikable rather than critical”). To test this hypothesis, we used a neuropsychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…This study corroborates the pathophysiological importance of the RSATL for MDD. 10 The finding that self-blameselective changes in RSATL connectivity are associated with vulnerability to MDD recurrence is in keeping with the hypothesis that deficient integration of conceptual social knowledge detail (eg, what it means to act "stingily") increases proneness to overgeneralized self-blame (eg, "I acted badly"), 17,20 described as a central cognitive feature of MDD. 4,38 This result is compatible with the view that the RSATL may implicitly enrich moral feelings such as guilt with detailed implicit social meaning (ie, social conceptual representations) even in the absence of verbalization.…”
Section: Discussionsupporting
confidence: 58%
“…This study corroborates the pathophysiological importance of the RSATL for MDD. 10 The finding that self-blameselective changes in RSATL connectivity are associated with vulnerability to MDD recurrence is in keeping with the hypothesis that deficient integration of conceptual social knowledge detail (eg, what it means to act "stingily") increases proneness to overgeneralized self-blame (eg, "I acted badly"), 17,20 described as a central cognitive feature of MDD. 4,38 This result is compatible with the view that the RSATL may implicitly enrich moral feelings such as guilt with detailed implicit social meaning (ie, social conceptual representations) even in the absence of verbalization.…”
Section: Discussionsupporting
confidence: 58%
“…Next, we found that the negative indirect effect of pain intensity on QoL was through depression. The imaging studies on human found that many brain areas involved in pain and depression were overlaped, such as primary and secondary somatosensory cortex, anterior cingular cortex, hippocumpus and so on (Doan, Manders, & Wang, ; Green et al, ; Ushinsky, Reinhardt, Simmons, & Strigo, ; Zeng et al, ). Animal studies, based on NeP induced depression model, revealed that some common neuroplasticity changes were shared between pain and depression in central nerve system and the underlying mechanism included monoamine neurotransmitters, inflammatory factors and glutamate and its receptors (Doan et al, ; Humo, Lu, & Yalcin, ; Sheng, Liu, Wang, Cui, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with existing meta-analyses showing that women tend to experience negative emotions, such as guilt, more intensely than men (Else-Quest et al, 2012 ). This task may therefore be useful in understanding gender differences in treatment outcomes, particularly in terms of self-blame biases and their suggested link to a vulnerability to depression (Green et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%